1992
DOI: 10.1108/eum0000000000639
|View full text |Cite
|
Sign up to set email alerts
|

Country‐of‐Origin Stereotyping: A Case Study in the New Zealand Motor Vehicle Industry

Abstract: Focuses on the issue of country of origin stereotyping by consumers in the New Zealand automobile market. The approach uses 275 mail questionnaires (with 150 of these being returned) containing bi‐polar adjectives to assess the current attitude of new car purchasers towards automobiles made in four different countries (France, Italy, Germany and Japan). These four countries were chosen on the basis of their brand and model representation in the New Zealand market. The results of the study indicate that there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 7 publications
0
55
0
2
Order By: Relevance
“…A study of the New Zealand new automobile market showed that country-of-origin stereotyping was present in the New Zealand new car market and that it was often a determining factor in the buying process (Lawrence, Marr, & Prendergast, 1992). However, as Parameswaran and Yaprak (1987) have shown, the reliability of scale ratings of product attributes may differ among different countries.…”
Section: Literature Reviewmentioning
confidence: 97%
“…A study of the New Zealand new automobile market showed that country-of-origin stereotyping was present in the New Zealand new car market and that it was often a determining factor in the buying process (Lawrence, Marr, & Prendergast, 1992). However, as Parameswaran and Yaprak (1987) have shown, the reliability of scale ratings of product attributes may differ among different countries.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Some studies found a distinct nationalistic trend in perceptions (e.g., Darling and Kraft 1977;Suh and Kwon 2001); others found country stereotypes to be universally held (e.g., Heslop and Papadopoulos 1993). Some researchers suggest that country stereotypes are used as a heuristic to simplify choice (Lawrence, Marr, and Prendergast 1992), although they may lead to erroneous perceptions of foreign products (Johansson, Ronkainen, and Czinkota 1994). Janda and Rao (1997) conceptualized COO effects as resulting from two separate processes: cultural stereotypes and personal beliefs.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…The COO macro image is a global-level variable and addresses a wide set of country associations, including national symbols, economic and political situations, levels of industrialization, and cultural values (Hooley et al, 1988;Lawrence et al, 1992;Papadopoulos and Heslop, 2003). The COO micro image is relative to a given product category (e.g., Italy and shoes) and reflects beliefs about the relationship between the country and the product category.…”
Section: Country-of-origin Imagesmentioning
confidence: 99%